Faceless after dark [videorecording (DVD)] - Kanell, Jenna; Kanell, Jenna; Jacobs, Todd; Kang, Danny; Lyn, Danielle (Dark Sky Films, 2024)
Following her breakout success as the star of a killer clown horror flick, Bowie now finds herself struggling to capitalize on its success. Suddenly held hostage by an unhinged fan posing as that same killer clown, horror becomes her reality as she fights to survive the night and escape before he completes his sinister plan to recreate the film's fatal plot.